Parts of hire contract to supply specific software: Comparative Study - الساعدي جليل حسن; شنيشل حوراء كطان (Journal of Legal Sciences, 2019)
The aim of this study is to know the capability of the Iraqi system law, to organize contracts of supplying software especially the contract of designing or developing software, according to the requirements of somebody. The specific software features than typical software, where the later imported as a goods, while the incoming contract to designing or developing specific software represents employment contract, in this case leads to a complicated problems of the type of contract, the later contract may interact with sale contract and lease contract. Hire contract applies to the contract of this study, where supplier to these software is contractor and the person who designed the required software, as a result this study can be divided into two parts: In The first part we discussed the concept of the hire contract of specific software, and in the second part we discussed the contracts parts.